Handbook of coal analysis - Speight, James G. (Chemical analysis, 2015)
Provides users with everything they need to know about testing and analysis of coal -Includes new coverage on environmental issues and regulations as related to coal -Provides the reader with the necessary information about testing and analyzing coal and relays the advantages and limitations in understanding the quality and performance of coal -Explains the meaning of test results and how these results can predict coal behavior and its corresponding environmental impact during use -Includes a comprehensive Glossary which defines items in straightforward language that enable readers to better understand the terminology related to coal -Treats issues related to sampling, and accuracy and precision of analysis.